Activity of THC, CBD, and CBN on Human ACE2 and SARS-CoV1/2 Main Protease to Understand Antiviral Defense Mechanism - Pitakbut, Thanet; Nguyen, Gia-Nam; Kayser, Oliver (Planta Medica, 2021)
THC, CBD, and CBN were reported as promising candidates against SARS-CoV2 infection, but the mechanism of action of these three cannabinoids is not understood. This study aims to determine the mechanism of action of THC, CBD, and CBN by selecting two essential targets that directly affect the coronavirus infections as viral main proteases and human angiotensin-converting enzyme2. Tested THC and CBD presented a dual-action action against both selected targets. Only CBD acted as a potent viral main protease inhibitor at the IC50 value of 1.86 ± 0.04 µM and exhibited only moderate activity against human angiotensin-converting enzyme2 at the IC50 value of 14.65 ± 0.47 µM. THC acted as a moderate inhibitor against both viral main protease and human angiotensin-converting enzymes2 at the IC50 value of 16.23 ± 1.71 µM and 11.47 ± 3.60 µM, respectively. Here, we discuss cannabinoid-associated antiviral activity mechanisms based on in silico docking studies and in vitro receptor binding studies.
Keywords: Δ-9-Tetrahydrocannabinol; Cannabidiol; Cannabinol; coronavirus main protease1/2; human angiotensin-converting enzyme2; Cannabis sativa; Cannabaceae